2019
DOI: 10.1002/per.2198
|View full text |Cite
|
Sign up to set email alerts
|

Happy Like a Fish in Water? The Role of Personality–Situation Fit for Momentary Happiness in Social Interactions across the Adult Lifespan

Abstract: Growing research on personality-relationship dynamics demonstrates that people's personality and their (enjoyment of) social relationships are closely intertwined. Using experience sampling data from 136 adults (aged 18-89 years) who reported on more than 50 000 social interactions, we zoom into everyday real-world social interactions to examine how Big Five personality traits and social context characteristics shape people's happiness in social encounters across the adult lifespan. Results revealed that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 115 publications
(260 reference statements)
11
58
0
Order By: Relevance
“…Recently, due to the more widespread use of smartphones, such data collection is gaining popularity, yet there are still not many published studies assessing the impact of different social situations on people's well-being. In a recently published study, Mueller et al (2019) obtained similar results to those of Study 1. In fact, participants in Mueller and collaborators' study (2019) also used smartphones to provide information about each faceto-face interaction lasting more than five minutes, as well as their resulting momentary affect levels.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Recently, due to the more widespread use of smartphones, such data collection is gaining popularity, yet there are still not many published studies assessing the impact of different social situations on people's well-being. In a recently published study, Mueller et al (2019) obtained similar results to those of Study 1. In fact, participants in Mueller and collaborators' study (2019) also used smartphones to provide information about each faceto-face interaction lasting more than five minutes, as well as their resulting momentary affect levels.…”
Section: Discussionsupporting
confidence: 77%
“…Since the participants of Study 1 were predominately young university students, the strong negative feelings when not speaking to strong-ties could have been a result of participants' conflicts with parents or other family members. Studies pointed out that among strong-ties, people reported more positive affect when being around friends than when interacting with their families, and this association becomes more prevalent as people mature (Chui et al, 2014;Csikszentmihalyi & Hunter, 2003;Larsen, Mannell, & Zuzanek, 1986;Mueller et al, 2019). This is understandable, since being with friends is predominately associated with leisure activities, an ability to choose those activities and one's companions, while being with family is often underlined by duties, routines, and not always being around like-minded people (Larson et al, 1986;Saphire-Bernstein & Taylor, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, theoretically, the affiliative aspect of extraversion should predict greater enjoyment of warm, affectionate social interactions, whereas the agentic aspect may predict positive affect in social situations where goal pursuit and reward are especially salient. Future studies could investigate the extent to which specific aspects of extraversion-and other personality traits (e.g., neuroticism; Mueller et al, 2019;Shackman et al, 2018)-moderate the association between different aspects of social interactions and well-being.…”
Section: Searching For a Moderating Role Of Trait Extraversionmentioning
confidence: 99%